How to use dianetics based on the #1 New York Times bestseller by L. Ron Hubbard - Hubbard, L. Ron (La Fayette Ron) 1911-1986 (Golden Era Productions, 2010)
DVD and accompanying booklet provide introductory information on how to use Dianetics.